Semi‐end‐to‐end esophagojejunostomy after laparoscopy‐assisted total gastrectomy better reduces stricture and leakage than the conventional end‐to‐side procedure: A retrospective study. Issue 2 (18th April 2017) - Duan, Wei; Liu, Kaijun; Fu, Xiaolong; Shen, Xuqi; Chen, Jun; Su, Chongyu; Yu, Peiwu; Zhao, Yongliang
Abstract : Background and Objective: Laparoscopy‐assisted total gastrectomy (LATG) has not gained popularity due to the technical difficulty of esophagojejunostomy (EJ) and the high incidence of EJ‐related complications. Herein, we compared two types of EJ for Roux‐en‐Y reconstruction to determine whether semi‐end‐to‐end (SETE) EJ is more convenient than the end‐to‐side (ETS) procedure and is capable of reducing stricture and leakage. Methods: A total of 268 patients who underwent LATG with Roux‐en‐Y reconstruction were included in this study. Two types of EJ were applied for LATG: conventional ETS EJ and SETE EJ. The surgical outcomes and postoperative complications were compared. Results: The mean reconstruction time in the SETE group was shorter than that in the ETS group (41.6 ± 8.0 min vs 51.3 ± 9.2 min, P = 0.000). The incidences of total EJ‐related complications, EJ leakage, and EJ stricture in the SETE group and ETS group were 1.1% (1/92) and 10.2% (18/176), 1.1% (1/92) and 4.0% (7/176), and 0 and 6.2% (11/176), respectively. The incidence of total EJ‐related complications in the SETE group was lower than that of the ETS group ( P = 0.006), and the incidence of EJ stricture in the SETE group was lower than that of the ETS group ( P = 0.034). Conclusions: SETE EJ is more convenient than the conventional ETS procedure and is associated with a shorter reconstruction time and a lower incidence of EJ stricture and leakage.